Analysis of Flood Management Effectiveness Through the Implementation of Drainage Revitalization Policies: A Systematic Literature Review - Sofia Ayu Anggraini Sulu Lazar; Irwan Noor; Niken Lastiti V.A (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Urban flooding has become increasingly frequent due to rapid urbanization, climate change, and the limited capacity of drainage infrastructure, prompting growing scholarly attention to the effectiveness of drainage revitalization policies across countries. However, the literature examining the relationship between policy implementation and flood management effectiveness remains fragmented across different disciplines and methodological approaches, and has not yet been systematically synthesized. This study aims to identify, evaluate, and synthesize scientific literature on the effectiveness of flood management through the implementation of drainage revitalization policies, using a Systematic Literature Review (SLR) approach based on the PRISMA 2020 framework. Literature searches were conducted in Google Scholar, ScienceDirect, MDPI, and Scopus databases using the keywords policy implementation, drainage revitalization, flood management effectiveness, and flood management policy implementation, resulting in 41 relevant articles selected from an initial pool of 312 studies after undergoing the stages of identification, screening, eligibility assessment, and inclusion. The synthesis identified four major themes influencing flood management effectiveness through drainage revitalization: governance and institutional coordination; technical and infrastructural capacity; community participation and social adaptation; and approaches based on natural processes and geomorphology. The findings indicate that the success of drainage policies is consistently determined by the quality of implementation, particularly communication, resources, implementers' disposition, and bureaucratic structure, as proposed by Edwards III (1980), rather than solely by the scale of investment in physical infrastructure. This study concludes that flood management effectiveness results from a multidimensional interaction among policy quality, infrastructure performance, and institutional capacity. Therefore, future evaluations of drainage policies should integrate these three dimensions simultaneously to achieve more effective and sustainable urban flood management.